Heightened perception of competition hastens courtship. (29th October 2019) - Santori, Claudia; Bussière, Luc F; Houslay, Thomas M
Abstract: When animals use costly labile display or signal traits to display to the opposite sex, they face complex decisions regarding the degree and timing of their investment in separate instances of trait expression. Such decisions may be informed by not only the focal individual's condition (or pool of available resources) but also aspects of the social environment, such as perceptions of same-sex competition or the quality of available mates. However, the relative importance of these factors to investment decisions remains unclear. Here, we use manipulations of condition (through dietary nutrition), recent social environment (exposure to a silenced male, nonsilenced male, female, or isolation), and female mating history (single or multiple male) to test how quickly male decorated crickets ( Gryllodes sigillatus ) decide to begin courting an available female. We find that males that were previously housed with nonsilenced males started courting the female earlier than other males. Females only mounted males after courtship began. Our results suggest a strong effect of the perception of competition on the decision to invest resources in sexual signaling behavior and that females might exert directional selection on its timing. Lay Summary: Animals must make decisions about when and how much energy to invest in different activities, including courting potential mates. Male crickets recently housed with another male started courting an available female earlier than males housed with females or isolated. The perception of competition had a stronger effect than the male's own condition or the mating status of the female. Males that did not court the available female during observations were never mated.